Phosphorus post-functionalization of diphosphahexaarenes - Hindenberg, Philip; Rominger, Frank; Romero-Nieto, Carlos (Chemistry - a European journal)
Diphosphahexaarenes are highly stable π-extended frameworks containing two six-membered phosphorus heterocycles that have emerged recently. Herein, we present a detailed investigation on the post-functionalization reactions of their phosphorus centers with special emphasis on the selectivity of the processes and the impact of the phosphorus functionalizations into the physicochemical properties. These studies reveal that indeed the phosphorus atoms of the diphosphahexaarenes are readily available to be functionalized with quaternizing and oxidizing agents as well as borane groups without compromising the stability of the system. In addition, the optoelectronic properties of the diphosphahexaarenes are impacted by the phosphorus post-modifications.